The Impact Of Oil Sector On The Arab National Security Degree (Arab Oil Countries)The Period 1980-2021) - صقر جعفر (Latakia University Journal - Economic and Legal Sciences Series, 2024)
In this study the researcher studies the impact of oil sector on Arab national security in Arab oil countries, which is aiming to determine the aspects of the relationship between oil sector variables, and the percentage of national security index, which was promoted by USA national security agency, The importance of this study comes by applying on Arab countries state, The researcher did a multi regression model between the exports and imports of crude oil and refined oil products as independent variables represents oil sector, and Arab national security as dependent variable, The result is positive relationship between the exports and imports of refined oil products with the national security index, and there is not a significant impact of crude oil over Arab national security, and this shows the importance of enhancing the refined products sector in Arab countries, and its role in increasing national security, specially exporting refined oil products.